Persistence of Underrepresented Minorities in STEM Fields: Are Summer Bridge Programs Sufficient? - Ghazzawi, Dina; Pattison, Donna; Horn, Catherine (Frontiers in Education, 2021)
This study examines the extent to which participation in an NSF funded STEM intervention program can impact the long-term persistence and graduation of first-time in college under-represented minority students. Using discrete-time competing risks analysis, results demonstrated that participants of the intervention program had a lower probability of drop out and higher probability of persisting in a STEM field of study compared to non-participants of the program. Findings also highlight the importance of early academic preparation in Calculus and total credit accumulation to student success outcomes of URM students enrolled in STEM fields.